Relationships between university professors and students: Should they be banned?. Issue 2 (4th May 2017) - McArthur, Neil
Abstract: This article examines the question of whether universities and colleges should attempt to ban all student-faculty relationships, as many have tried to do. It argues that, because adults have a fundamental right to engage in intimate relationships without interference, supporters of relationship bans must meet a high standard in defending them. But outright bans on such relationships cannot meet this standard. Though the desire to create a secure environment for students is legitimate and important, it cannot be shown that relationship bans are necessary or proportional means of doing so. Besides being a violation of the rights of the people involved, relationship bans have a negative impact on the larger university community. The argument is not a defense of such relationships per se. Romantic interactions between students and faculty are invariably complicated and perilous, and should be approached with caution.